Penerapan Grasi Dalam Perspektif Hukum Pidana Bagi Terdakwa - Wibowo, Aryo; Syahlahaifa , Zahra; Hosnah, Asmak (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2024)
In the presidential system of government, there are prerogative rights that are only owned by the head of state as the leader of the country. Clemency is regulated under Law Number 5 of 2010 on Clemency on the amendement of Law Number 22 of 2022 on Clemency. One of the uses of prerogative rights is to provide relief to several convicts by granting clemency. The granting of clemency by the President is based on humanity and without any interference from other parties or other state institutions. Although the granting of clemency is in the hands of the President due to the ownership of the prerogative, the consideration of granting clemency must be considered by the Supremen Court, the Prosecutor, and the Minister of Law and Human Rights so that there is cooperation between the relevant legal institutions. Clemency is utilized by several convicts, especially death row convicts, to cut the sentence imposed on them so that the executive of the sentence becomes shorter from the first time the decision is read out by the judge at the first level court.